Pengaruh e–service quality dan relationship marketing terhadap loyalitas nasabah dengan komitmen sebagai variabel intervening di BMT NUKAS - Nadifah, Nurul Ahillatun; Amir, Faizal (Universitas Widya Mataram, 2025)
This study aims to analyse the effect of e-service quality and relationship marketing on customer loyalty at BMT NUKAS with customer commitment as an intervening variable. A quantitative approach was applied in this study with hypothesis testing using Smart PLS. Data were collected through questionnaires filled out by 163 BMT NUKAS customers. The results showed that electronic service quality had no significant effect on customer commitment (p = 0.138), while relational marketing also had no effect on customer commitment. However, relational marketing had an effect on customer loyalty (p = 0.016), as did e-service quality (p = 0.027). Customer loyalty is also influenced by customer commitment with p = 0.000. However, e-service quality does not directly influence customer loyalty through the mediation of customer commitment (p = 0.180), while relational marketing has a significant influence on customer loyalty through the mediation of customer commitment (p = 0.000). These findings indicate that BMT NUKAS needs to strengthen relationships with customers to build trust and effective communication to increase customer loyalty. In addition, improvements in e-services, including ease of use, transaction security, and responsiveness to customer complaints, are important factors in creating sustainable customer loyalty.